Laboratory of technologies and learning of programming and robotics for pre and primary school - Pinto, M. Santos Miranda (2017)
This research intends to study how to integrate programming and robotics in kindergartens and primary schools, through a transversal intervention in all the areas of knowledge. This will allow the development of a theoretical framework based on research, able to support the formulation of a proposal of intervention extended to the Portuguese national context. For this project, we will be designing a physical and a mobile laboratory, equipped with tablets and robots, which will facilitate, on the one hand, the initial, postgraduate and continuous training of teachers and, on the other hand, the accomplishment of several case studies throughout Portugal. In addition, the training of teachers and also the participation of the children in the expected activities of this project will enable the designing a theoretical framework about the development of a competences profile for education professionals in this area.